BAP1 suppresses prostate cancer progression by deubiquitinating and stabilizing PTEN. Issue 1 (20th November 2020) - Deng, Rong; Guo, Yanmin; Li, Lian; He, Jianfeng; Qiang, Zhe; Zhang, Hailong; Chen, Ran; Wang, Yanli; Zhao, Xian; Yu, Jianxiu
Abstract : Deubiquitinase BAP1 is an important tumor suppressor in several malignancies, but its functions and critical substrates in prostate cancer (PCa) remain unclear. Here, we report that the mRNA and protein expression levels of BAP1 are downregulated in clinical PCa specimens. BAP1 can physically bind to and deubiquitinate PTEN, which inhibits the ubiquitination‐mediated degradation of PTEN and thus stabilizes PTEN protein. Ectopically expressed BAP1 in PCa cells increases PTEN protein level and subsequently inhibits the AKT signaling pathway, thus suppressing PCa progression. Conversely, knockdown of BAP1 in PCa cells leads to the decrease in PTEN protein level and the activation of the Akt signaling pathway, therefore promoting malignant transformation and cancer metastasis. However, these can be reversed by the re‐expression of PTEN. More importantly, we found that BAP1 protein level positively correlates with PTEN in a substantial fraction of human cancers. These findings demonstrate that BAP1 is an important deubiquitinase of PTEN for its stability and the BAP1‐PTEN signaling axis plays a crucial role in tumor suppression. Abstract : PTEN protein levels are regulated through ubiquitination. Here, we identify BAP1 as a deubiquitinase that physically binds to and deubiquitinates PTEN, thereby inhibiting PTEN degradation. Stabilized PTEN suppresses prostate cancer progression by inhibiting Akt phosphorylation.